2020
DOI: 10.1002/fuce.201900189
|View full text |Cite
|
Sign up to set email alerts
|

The Asymmetric Effects of Cu2+ Contamination in a Proton Exchange Membrane Fuel Cell (PEMFC)

Abstract: In this work, we investigate the effects of Cu 2+ contamination on the cathode, anode and membrane of a 50 cm 2 acitve area membrane electrode assembly (MEA) in a proton exchange membrane fuel cell (PEMFC), by using carbon supported dealloyed PtCu 3 nanoparticles as the cathode electrocatalysts. PtCu 3 is dealloyed with nitric acid at 25°C and 80°C for different dealloying harshness. It is found that the MEA with the catalyst dealloyed at 25°C has a higher performance at low current density region, while it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Similar observations on the presence of Cu in the membrane and in the anode have been reported recently 39 . One possible solution to mitigate this has been demonstrated by P. Mani and co-workers 40 , where an already fabricated CCM was exposed to another round of acid washing.…”
Section: Introductionsupporting
confidence: 89%
“…Similar observations on the presence of Cu in the membrane and in the anode have been reported recently 39 . One possible solution to mitigate this has been demonstrated by P. Mani and co-workers 40 , where an already fabricated CCM was exposed to another round of acid washing.…”
Section: Introductionsupporting
confidence: 89%
“…Furthermore, due to very low carbon solubility in Cu ( Li et al., 2009 ), encapsulation of Pt-M nanoparticles with a carbon shell due to high-temperature treatments necessary for (intermetallic) Pt-alloy formation is not a concern. On the downside, many negative effects of Cu ions on the PEMFC performance have been shown ( Yu et al., 2012 ; Zhu et al., 2020 ). Thus, for even the slightest possibility of sensible and successful implementation of Pt-Cu alloy electrocatalysts in the industry, significant improvements in stability of Pt-alloys during real-time operation.…”
Section: Resultsmentioning
confidence: 99%
“…One such example is the interaction between the dissolved M ions and Pt surface that blocks the active surface and thus affects its electrochemical performance. In this sense, the most prominent example can be shown in the case of Pt-Cu alloy where Cu ions strongly interact, namely adsorb and reduce, on the Pt surface via well-known under-potential deposition (UPD); Cu can be found on both the cathode and the anode ( Gatalo et al., 2019a , 2019b ; Jia et al., 2013 ; Yu et al., 2012 ; Zhu et al., 2020 ). The second example is the replacement of protons in the ionomer with M cations, which results in higher O 2 resistance as well as changes the water-uptake that consequently lowers the proton conductivity of the ionomer ( Braaten et al., 2017 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Cu ions released from the cathode would accumulate as Cu 2+ at the cathode, and also could migrate into the PEM and redeposited as metallic Cu on the surface of the anode Pt, especially at the operation at high current density and low humidity, as shown in Figure a,b. [ 127 ] The deposition of metallic Cu in an anode could suppress the hydrogen adsorption which severely hinders the HOR. For the typically used PtCo/C catalyst in commercial vehicles, it was found that the PtCo suffered from a degradation mechanism slightly different from the Pt/C (Figure 7c,d).…”
Section: Durability Issues In Meamentioning
confidence: 99%